Waterfowl Populations in Eastern Lancaster Sound and Western Baffin Bay - McLaren, Peter L.; McLaren, Margaret A. (ARCTIC, 1982)
The seasonal distributions of oldsquaws (Clangula hyemalis), common eiders (Somateria mollissima) and king eiders (S. spectabilis) were determined through aerial surveys in eastern Lancaster Sound (1976, 1978 and 1979) and northwest Baffin Bay (1978, 1979). Sightings of geese are summarized in an Appendix. The major spring influx of both eiders occurs about the second week of May but most oldsquaws do not arrive until the first half of June. In spring, all three species are rare in offshore areas, are most abundant along coasts in the northern half of the study area, and tend to depart to nesting areas during the last week of June. Oldsqaws molt along coasts of Lancaster Sound and northwest Baffin Bay, but both species of eiders undertake molt migrations. Three waves of eider out-migration were detected in 1976 and 1978. Distribution and movements within the study area are related to probable migrations routes and ice conditions.Key words: oldsquaw, king eider, common eider, geese, aerial surveys, distribution, molt migration, eastern Arctic, Baffin Bay, Lancaster Sound